2012
DOI: 10.1242/dev.081885
|View full text |Cite
|
Sign up to set email alerts
|

Dishevelled limits Notch signalling through inhibition of CSL

Abstract: Notch and Wnt are highly conserved signalling pathways that are used repeatedly throughout animal development to generate a diverse array of cell types. However, they often have opposing effects on cell-fate decisions with each pathway promoting an alternate outcome. Commonly, a cell receiving both signals exhibits only Wnt pathway activity. This suggests that Wnt inhibits Notch activity to promote a Wnt-ON/Notch-OFF output; but what might underpin this Notch regulation is not understood. Here, we show that Wn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 64 publications
2
62
0
Order By: Relevance
“…Interestingly, ENCCs secrete WNT ligands (Serralbo and Marcelle, 2014) and WNT signaling is essential for stomach development (Theodosiou and Tabin, 2003). Furthermore, it has been shown that WNT signaling limits Notch activity in cell culture (Collu et al, 2012;Liu et al, 2013b), supporting the idea that WNT ligands secreted from vENCCs could activate WNT signaling in the mesenchyme, which in turn could lead to the inhibition of Notch activity. Testing this hypothesis would first imply an analysis of the expression of multiple WNT ligands in our system to determine which one(s) is (are) expressed in the vENCCs in order to examine to what extent the modulation of WNT activity specifically in the mesenchyme affects both stomach patterning/differentiation and Notch activity.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, ENCCs secrete WNT ligands (Serralbo and Marcelle, 2014) and WNT signaling is essential for stomach development (Theodosiou and Tabin, 2003). Furthermore, it has been shown that WNT signaling limits Notch activity in cell culture (Collu et al, 2012;Liu et al, 2013b), supporting the idea that WNT ligands secreted from vENCCs could activate WNT signaling in the mesenchyme, which in turn could lead to the inhibition of Notch activity. Testing this hypothesis would first imply an analysis of the expression of multiple WNT ligands in our system to determine which one(s) is (are) expressed in the vENCCs in order to examine to what extent the modulation of WNT activity specifically in the mesenchyme affects both stomach patterning/differentiation and Notch activity.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, in mammalian cells Wnt signaling can inhibit CSL activity by direct binding of Dishevelled, and CSL stability is regulated by Presenilin-2 and p38 MAP-kinase, while its cellular localization can be regulated in Xenopus laevis or mammalian cells by RITA or SMRT protein complexes. [8][9][10][11] Recent advances in human genomic and transcriptomic analyses provide insights into individual differences in susceptibility to disease, with tissue-specific control of gene expression as key determinant. 12 For novel insights into control of CSL gene expression, we started from the study of individual variations in gene expression in human dermal fibroblasts (HDFs) derived from many different individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The network of several main signaling molecules [15,21,25,[33][34][35][36][37] that may regulate the proliferation and differentiation of NSCs is shown in Figure 1.…”
Section: Hist One Modificationmentioning
confidence: 99%